Empowering Higher Order Mathematical Thinking Skills with the e-PINTER Model in Blended Learning - Kurniawan, Heru; Darminto, Bambang Priyo (FKIP Universitas Lampung, 2022)
This study aims to determine whether the e-PINTER mathematics learning model can improve students' higher-order thinking skills in blended learning settings. The population of this study was all seventh-grade students of Junior High School (SMP) in Purworejo Regency. The research design used a one-group pre-test and post-test design to determine the improvement of higher-order thinking skills. The sampling technique used was stratified cluster random sampling, so that the students of SMP 5 Purworejo, SMP N 11 Purwoprejo, and SMP N 23 Purworejo were obtained as research samples. The data analysis technique used paired t tests. The results showed that the application of the e-PINTER mathematics learning model could improve students' higher-order thinking skills in blended learning settings. The results of the study have a significant effect on learning mathematics so the empowerment of students' higher-order thinking skills in mathematics should be the center of attention for learning mathematics as a whole. Keywords: e-PINTER learning model, blended learning, higher-order thinking skills. DOI: http://dx.doi.org/10.23960/jpmipa/v23i2.pp832-841